Impact of surgeon’s experience in rigid versus elastic MRI/TRUS-fusion biopsy to detect significant prostate cancer using targeted and systematic cores - Görtz, Magdalena; Nyarangi-Dix, Joanne; Pursche, Lars; Schütz, Viktoria; Reimold, Philipp; Schwab, Constantin; Stenzinger, Albrecht; Sültmann, Holger; Duensing, Stefan; Schlemmer, Heinz-Peter; Bonekamp, David; Hohenfellner, Markus; et al. (Cancers, 2022)
Multiparametric magnetic resonance imaging (mpMRI) and MRI/ultrasound fusion-targeted prostate biopsy (FB) have excellent sensitivity in detecting significant prostate cancer (sPC). FB platforms can be distinguished by rigid (RTB) or elastic image registration (ETB). We compared RTB and ETB by analyzing sPC detection rates of both RTB and ETB at different stages of the surgeons’ learning curve. Patients undergoing RTB between 2015-2017 (n = 502) were compared to patients undergoing ETB from 2017-2019 (n = 437). SPC detection rates were compared by Chi-square-test on patient-basis. Combination of transperineal systematic biopsy and each TB served as reference and sub-analyses were performed for different grades of surgeon’s experience. In the RTB subgroup, 233 men (46%) had sPC, compared to 201 (46%) in the ETB subgroup. RTB alone detected 94% of men with sPC and ETB 87% (p = 0.02). However, for at least intermediate-experienced surgeons (>100 FB), no differences occurred between RTB and ETB. In the total cohort, at least intermediate-experienced surgeons detected significantly more sPC (10%, p = 0.008) than novices. Thus, targeted transperineal MRI/TRUS-FB with a RTB registration system showed a similar sPC detection rate to ETB in experienced surgeons but a superior sPC detection rate to ETB in the total cohort. Low-experienced surgeons seem to benefit from RTB.
Gesehen am 25.04.2022